Rozwój człowieka – rozwój świata – refleksja w rocznicę wielkich papieskich encyklik społecznych - Stępniak, ks. Marek (Annales. Etyka w Życiu Gospodarczym, 2008)
The problem of the development of a human person and the whole mankind has a significantplace in the post Vaticanum Secundum social teaching of the Catholic church. This year’s anniversaryof two social encyclicals: Paul VI’s Populorum progressio (1967) and John Paul II’s Sollicitudo reisocialis (1987) indicates the need of undertaking theological and anthropological reflection uponthe process of development. The Catholic social teaching placing a human person in the center of allsocial, political and economic processes evaluates the quality of development from the perspective ofrespecting human dignity and rights.Although the development issues have originated from social teaching of local churches of Africaand Latin America, thanks to the social encyclicals it took on a global dimension.The social teaching of the Catholic church by indicating the need of the integral development ofa human person and the whole mankind, points out the problems of material, spiritual povertyand violation of human rights. Therefore, the teaching about development is an integral element ofthe preferential option for the poor in the ministry of the Catholic church.